Deposição de filmes finos tipo multicamadas Cr/TiN com diferentes arquiteturas e estudo de estrutura, propriedades tribológicas, resistência à oxidação e à corrosão - Soares, Vagner Fontes Gonçalves (2020)
Iso and non-iso architected Cr/TiN multilayers thin films with constant thickness and composition were deposited by magnetron sputtering aiming to study the influence of different architectures over coatings structures and properties. Glow-discharge optical emission spectroscopy (GD-OES) and scanning electron microscopy with field emission gun (SEM-FEG) analyses showed that all multilayers presented sharp interfaces and dense nanostructures, with columnar growth tendency and grain sizes varying according to layer thickness. Grazing Incidence X-Ray Diffraction (GAXRD) analyses showed that multilayers consist of polycrystalline α-Cr and δ-TiN phases with a preferential growth in Cr(110) plane. The overlapping of TiN onto metallic layers leads to a high amorphization degree of its structure, although TiN layers thicker than 50 nm demonstrated increased crystallinity in plane TiN(200). Nanohardness tests registered hardness values for all multilayers of around 16.2 GPa, evidencing that different distribution order of layers did not significantly influence this property. The low values of H/E noted in 0.08 indicate that all multilayers suffer nanoplastic deformations, being adequate only for non-contact or low intensity applications. Oxidation tests revealed the iso-structured architecture thin film presented an improved oxidation resistance due to a balance between Cr amount and TiN layers with modarate crystallinity at the upper period. Corrosion tests highlighted the graduated architecture with increasing amount of Cr towards the surface as the most suitable to optimize the corrosion resistance.